A Rare Case of Esophageal Rhabdomyoma Diagnosed by Fine-Needle Aspiration. (21st September 2018) - Robison, Ariane; Zhang, Ziying; Umar, Beena; Williamson, Sean; Perry, Kyle
Abstract: Introduction: Rhabdomyomas are rare benign tumors of striated muscle, which often present in the head and neck region of elderly patients, but they can also arise in the posterior mediastinum. We herein present a case of rhabdomyoma of the esophagus, which was diagnosed by fine-needle aspiration cytology. To date, only five cases of esophageal rhabdomyoma have been reported in the medical literature, and to our knowledge, our case is the first to be diagnosed by fine-needle aspiration. Methods: A 63-year-old woman presented to our institution for a second opinion after an incidental finding of an esophageal mass on chest CT scan for evaluation of upper respiratory infection. She subsequently underwent a PET scan, which showed nonspecific increased uptake in the GE junction. EGD showed a noncircumferential submucosal lesion with ill-defined margins in the upper to middle third of the esophagus. On EUS, the greatest dimension of the mass was 4.4 cm, and it appeared to originate in the lamina propria. The patient then underwent fine-needle aspiration for diagnosis. Results: In the aspirate, fragments of round- to polygonal-shaped neoplastic cells with small, round, and eccentrically placed nuclei and eosinophilic granular cytoplasm were seen. There was no evidence of mitotic activity or cytologic atypia. Immunohistochemically, the tumor exhibited myogenic differentiation (positive for desmin, negative for SMA). The differential diagnoses included adult rhabdomyoma and rhabdomyosarcoma. Based on bland morphology and low proliferative index, the features were felt to be most consistent with rhabdomyoma. Conclusion: Although rare, rhabdomyomas can occur in the esophagus. As EUS aspirations become more frequent, these tumors should not be mistaken for neoplasms with an epithelioid morphology.